STUDI IMPEDANSI LISTRIK PADA DIABETES MELLITUS` - Laily Ardhianti Putri; Ekowati Retnaningtyas; Shahdevi Nandar Kurniawan; Hani Susianti; Andry Gonius; Atika Windra Sari; Chomsin Sulistya Widodo (Jurnal Penelitian Pendidikan IPA, 2024)
Diabetes mellitus has raised concerns about structural and functional changes in blood cells, as well as changes in blood impedance. The purpose of this study is to investigate the relationship between electrical impedance values measured with the Bioelectrical Impedance Analyzer (BIA) in diabetes patients. Blood samples were collected from 5 healthy people and 5 diabetes patients for the study. Electrical impedance testing with a BIA. The impedance method determines the electrical properties of blood by measuring its resistance and reactance at various frequencies. The results of the BIA are analyzed and compared to body health parameters such as the blood glucose level index. The average electrical impedance value in diabetes mellitus patients measured at a frequency of 100 Hz to 100 kHz with a current injection of 10 μA was found to be lower than the average electrical impedance value in healthy people. This study shows that the electrical impedance value of diabetes mellitus patients is lower than the impedance value of healthy people. This is consistent with diabetes mellitus patients' blood glucose levels, which are higher than healthy people's blood glucose levels.